Turmoil at Turrialba Volcano (Costa Rica): Degassing and eruptive processes inferred from high‐frequency gas monitoring. Issue 8 (28th August 2016) - de Moor, J. Maarten; Aiuppa, A.; Avard, G.; Wehrmann, H.; Dunbar, N.; Muller, C.; Tamburello, G.; Giudice, G.; Liuzzo, M.; Moretti, R.; Conde, V.; Galle, B.
Abstract: Eruptive activity at Turrialba Volcano (Costa Rica) has escalated significantly since 2014, causing airport and school closures in the capital city of San José. Whether or not new magma is involved in the current unrest seems probable but remains a matter of debate as ash deposits are dominated by hydrothermal material. Here we use high‐frequency gas monitoring to track the behavior of the volcano between 2014 and 2015 and to decipher magmatic versus hydrothermal contributions to the eruptions. Pulses of deeply derived CO2 ‐rich gas (CO2 /Stotal > 4.5) precede explosive activity, providing a clear precursor to eruptive periods that occurs up to 2 weeks before eruptions, which are accompanied by shallowly derived sulfur‐rich magmatic gas emissions. Degassing modeling suggests that the deep magmatic reservoir is 8–10 km deep, whereas the shallow magmatic gas source is at 3–5 km. Two cycles of degassing and eruption are observed, each attributed to pulses of magma ascending through the deep reservoir to shallow crustal levels. The magmatic degassing signals were overprinted by a fluid contribution from the shallow hydrothermal system, modifying the gas compositions, contributing volatiles to the emissions, and reflecting complex processes of scrubbing, displacement, and volatilization. H2 S/SO2 varies over 2 orders of magnitude through the monitoring period and demonstrates that the first eruptive episode involved hydrothermal gases, whereas the second did not. Massive degassing (>3000 T/d SO2 and H2 S/SO2 > 1) followed, suggesting boiling off of the hydrothermal system. The gas emissions show a remarkable shift to purely magmatic composition (H2 S/SO2 < 0.05) during the second eruptive period, reflecting the depletion of the hydrothermal system or the establishment of high‐temperature conduits bypassing remnant hydrothermal reservoirs, and the transition from phreatic to phreatomagmatic eruptive activity. Key Points: A gas composition precursor to eruptions is identified Changes in gas compositions are associated with transitions in eruptive processes Magma depth and volume are constrained